Who needs environmental monitoring?. Issue 5 (1st June 2007) - Lovett, Gary M.; Burns, Douglas A.; Driscoll, Charles T.; Jenkins, Jennifer C.; Mitchell, Myron J.; Rustad, Lindsey; Shanley, James B.; Likens, Gene E.; Haeuber, Richard
Abstract : Environmental monitoring is often criticized as being unscientific, too expensive, and wasteful. While some monitoring studies do suffer from these problems, there are also many highly successful long‐term monitoring programs that have provided important scientific advances and crucial information for environmental policy. Here, we discuss the characteristics of effective monitoring programs, and contend that monitoring should be considered a fundamental component of environmental science and policy. We urge scientists who develop monitoring programs to plan in advance to ensure high data quality, accessibility, and cost‐effectiveness, and we urge government agencies and other funding institutions to make greater commitments to increasing the amount and long‐term stability of funding for environmental monitoring programs.